(untitled) (Journal of Surgical Sciences, 2019)
Laparoscopic cholecystectomy is one of the commonest surgical procedures carried out in the world now a days. Chronic cholecystitis in a patient with situs inversus totalis may pose diagnostic and therapeutic challenges specially while laparoscopic cholecystectomy is to be carried out. We discuss one such case and make an outline how the diagnosis was made and the pitfalls encountered during surgery and how they were overcome. Journal of Surgical Sciences (2015) Vol. 19 (2) : 82-84